Increase in level of special physical fitness of the athletes specialising in different combat sports (judo, sambo, combat sambo) through of crossFit training. - Osipov, A. Y.; Kudryavtsev, M. D.; Iermakov, S. S.; Jagiello, W. (Archives of Budo, 2018)
Background and Study Aim: The experts consider the level of athletes` special endurance development to the intensive training and competitive influences as the definite factor of success in competitive activity of athletes in the current context. The aim of this study is knowledge about possibility of significant increase in this motor ability of the athletes practicing different types of combat sports (judo, sambo, combat sambo).